Wpływ gatunków domieszkowych na wzrost i pokrój dębu szypułkowego (Quercus robur L.) w uprawie założonej metodą Szymańskiego - Andrzejczyk, Tadeusz; Głodowski, Zbigniew (Leśne Prace Badawcze, 2010)
The study involved a comparison of the height, diameter at breast height, slenderness ratio (H/D) and thickness of the thickest branches of 13-year-old pedunculate oak trees growing in a traditional row plantation (variant I) and group plantations established according to the modified Szymanski Method: without the admixture species (variant II), in admixture with linden (variant III) and spruce (variant IV). A single group consisted of 16 trees, planted at a spacing of 30 × 30 cm, group spacing: 6×6 m. The study was conducted in north-eastern Poland (Wipsowo Forest District; N: 53°57′, E: 20°41′). It has been shown that oaks growing in a group plantation show a greater average height and slenderness than in a traditional plantation. Peripheral (edge) and internal oaks in a group differed in growth, habit and quality. The presence of an admixture species between the groups made these differences smaller, contributing to an improvement in the quality of edge oaks. The competitive effects of an admixture species on oaks depends on the distance between them. Spruce planted in close proximity (1.5 m) was strongly competitive (inhibition of growth and increasing slenderness of edge oak trees). Linden planted at a distance of 3 m had a positive impact on the quality of oaks and did not cause inhibition of their growth.